Reduction in serum sphingosine 1-phosphate concentration in malaria - Punsawad, Chuchard (PLoS One, 2017)
Sphingosine 1-phosphate (S1P) is a lipid mediator formed by the metabolism of sphingomyelin which is involved in the endothelial permeability and inflammation. Although the plasma S1P concentration is reportedly decreased in patients with cerebral malaria, the role of S1P in malaria is still unclear. The purpose of this study was to examine the impact of malaria on circulating S1P concentration and its relationship with clinical data in malaria patients. Serum S1P levels were measured in 29 patients with P. vivax, 30 patients with uncomplicated P. falciparum, and 13 patients with complicated P. falciparum malaria on admission and on day 7, compared with healthy subjects (n = 18) as control group. The lowest level of serum S1P concentration was found in the complicated P. falciparum malaria group, compared with P. vivax, uncomplicated P. falciparum patients and healthy controls (all p < 0.001). In addition, serum S1P level was positively correlated with platelet count, hemoglobin and hematocrit levels in malaria patients. In conclusions, low levels of S1P are associated with the severity of malaria, and are correlated with thrombocytopenia and anemia. These findings highlight a role of S1P in the severity of malaria and support the use of S1P and its analogue as a novel adjuvant therapy for malaria complications.